Covalent Binding of Bone Morphogenetic Protein‐2 and Transforming Growth Factor‐β3 to 3D Plotted Scaffolds for Osteochondral Tissue Regeneration. Issue 12 (25th September 2017) - Di Luca, Andrea; Klein‐Gunnewiek, Michel; Vancso, Julius G.; van Blitterswijk, Clemens A.; Benetti, Edmondo M.; Moroni, Lorenzo
Abstract : Engineering the osteochondral tissue presents some challenges mainly relying in its function of transition from the subchondral bone to articular cartilage and the gradual variation in several biological, mechanical, and structural features. A possible solution for osteochondral regeneration might be the design and fabrication of scaffolds presenting a gradient able to mimic this transition. Covalent binding of biological factors proved to enhance cell adhesion and differentiation in two‐dimensional culture substrates. Here, we used polymer brushes as selective linkers of bone morphogenetic protein‐2 (BMP‐2) and transforming growth factor‐β3 (TGF‐β3) on the surface of 3D scaffolds fabricated via additive manufacturing (AM) and subsequent controlled radical polymerization. These growth factors (GFs) are known to stimulate the differentiation of human mesenchymal stromal cells (hMSCs) toward the osteogenic and chondrogenic lineages, respectively. BMP‐2 and TGF‐β3 were covalently bound both homogeneously within a poly(ethylene glycol) (PEG)‐based brush‐functionalized scaffolds, and following a gradient composition by varying their concentration along the axial section of the 3D constructs. Following an approach previously developed by our group and proved to be successful to generate fibronectin gradients, opposite brush‐supported gradients of BMP‐2 and TGF‐β3 were finally generated and subsequently tested to differentiate cells in a gradient fashion. The brush‐supported GFs significantly influenced hMSCs osteochondral differentiation when the scaffolds were homogenously modified, yet no effect was observed in the gradient scaffolds. Therefore, this technique seems promising to maintain the biological activity of growth factors covalently linked to 3D scaffolds, but needs to be further optimized in case biological gradients are desired. Abstract : 3D scaffolds coupled to biological factors such as growth factors could have the potential to steer cell activity. Homogeneous covalent binding of growth factors showed enhanced gene expression for cartilage and bone tissue regeneration, associated to increased protein synthesis for bone regeneration. The possibility to create covalently bound gradients of growth factors is also explored. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB, visitwww.afob.org .